(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2009)
This research aims to study knowledge management as a strategy to raise the standard of living in social organizations, in this case study is Homeownership EAP, financial company, where there is a design tailored to the technical structure the "Balanced Scorecard" by Kaplan and Norton, in conjunction with the classification proposed by Mintzberg theory, design efficient structures, which represents the management strategies that allows for greater market competitiveness and high quality of life of people. A questionnaire was the manager of each level and concludes that the organization under study is characterized by a structure that is derived from the combination of the professional bureaucracy Organization Machine Bureaucracy.